2016
DOI: 10.1186/s12870-016-0789-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of grapevine seedless segregants during berry development reveals candidate genes associated with berry weight

Abstract: BackgroundBerry size is considered as one of the main selection criteria in table grape breeding programs. However, this is a quantitative and polygenic trait, and its genetic determination is still poorly understood. Considering its economic importance, it is relevant to determine its genetic architecture and elucidate the mechanisms involved in its expression. To approach this issue, an RNA-Seq experiment based on Illumina platform was performed (14 libraries), including seedless segregants with contrasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 80 publications
1
37
0
Order By: Relevance
“…() recently discovered new quantitative trait loci for berry weight or seed traits in grapevine, and mapped in these quantitative trait loci genes related to cell wall modifications, water import, auxin and ethylene signaling, transcription control, and organ identity. Likewise, recently, genes involved in the same pathways have been found differentially expressed in grapevine seedless segregants during berry development (Muñoz‐Espinoza et al ., ), thus our results support the hypothetical role of these genes in berry weight and development.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…() recently discovered new quantitative trait loci for berry weight or seed traits in grapevine, and mapped in these quantitative trait loci genes related to cell wall modifications, water import, auxin and ethylene signaling, transcription control, and organ identity. Likewise, recently, genes involved in the same pathways have been found differentially expressed in grapevine seedless segregants during berry development (Muñoz‐Espinoza et al ., ), thus our results support the hypothetical role of these genes in berry weight and development.…”
Section: Resultssupporting
confidence: 86%
“…Similarly, we found polymorphisms related to seedlessness and berry size in genes involved in auxin/hormone response, berry growth and development. Noteworthy, association mapping studies and expression data revealed candidate genes for berry weight involved in such similar pathways (Muñoz‐Bertomeu et al ., ; Doligez et al ., ; Muñoz‐Espinoza et al ., ). Our present results support the proposed role of these pathways in such complex traits and highlight new hypothetical candidate genes for further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Recently we reported and identified a group of candidate genes associated with berry size using transcriptomic data. The candidate genes encode for bHLH transcription factors, a GDSL esterase/lipase, a stilbene synthase, HSP17.9-D, among others [20]. Despite these findings, the genetic determinism and the molecular mechanisms behind berry development are complex and futher analysis and data are required to reveal their genetic architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome sequencing is an effective method for genome-wide detection of potential participants of complex traits [18][19][20][21][22][23][24][25][26][27]. Dozens of studies in the field of fruit development and nutrition have implemented sequencing technologies [28][29][30]. In view of these facts, the work presented here was performed to uncover the key phytonutrient-associated genes and their regulators in elm fruit.…”
Section: Introductionmentioning
confidence: 99%